Wire rod for rack bar and manufacturing method thereof

KR103019762B1Active Publication Date: 2026-09-16HYUNDAE STEEL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020240003830
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-01-09
Publication Date
2026-09-16
Estimated Expiration
2044-01-09

Smart Images

  • Figure 112024003259896-PAT00001_ABST
    Figure 112024003259896-PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a wire for a rack bar comprising, in weight percent, C: 0.40~0.55%, Si: 0.10~0.40%, Mn: 1.00~1.50%, V: 0.01~0.20%, Cr: 0.05~0.30%, Ni: 0.05~0.30%, Al: 0.01~0.05%, S: 0.03~0.07%, Mo: 0.005~0.30%, and the remainder being Fe and unavoidable impurities, wherein the Cr and V satisfy the composition of the following formula (1), and in a cross-section perpendicular to the longitudinal direction of the wire, where the diameter of the wire is D and the carbon content at depths of 0.1D, 0.3D, and 0.5D from the surface of the wire toward the center is C0.1D, C0.3D, and C0.5D, respectively, satisfying the following formulas (2) and (3). and a method for manufacturing the same is provided. 0.10 ≤ [Cr]+[V] ≤ 0.50 … Equation (1) 0.9 ≤ C0.1D / C0.3D ≤ 1.1 … Equation (2) 0.9 ≤ C0.3D / C0.5D ≤ 1.1 … Equation (3) The above [Cr] and [V] represent the content (weight%) of Cr and V, respectively.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a wire rod for a rack bar and a method for manufacturing the same, and more specifically, to a wire rod used in an automobile steering rack bar having excellent mechanical properties and impact toughness even without heat treatment, and a method for manufacturing the same. Background Technology

[0002] The material used for high-strength / high-toughness rack bars in conventional automotive steering systems has generally been tempered steel, which is produced by quenching and tempering medium-carbon steel in the austenite region to improve the material's strength and toughness. Conventional tempered steel products for steering racks are manufactured through a process involving raw material → drawing → filling → machining → high-frequency heat treatment → straightening → steering rack bar.

[0003] However, due to the recent increase in the strength of rack bars and automotive parts, the wear of machining and grinding materials during the processing of rack bar gear teeth is increasing. Furthermore, since heat treatment is applied locally only to the gear teeth, thermal deformation occurs, making correction work essential. In the case of rack bar components, when high-frequency heat treatment is applied, the thermal deformation zone (depth) differs between the tooth face and the back face due to the gear shape; this leads to thermal deformation and requires correction. However, since significant differences in carbon content—which greatly influences heat treatment characteristics—between the tooth face and the back face result in substantial thermal deformation, increasing the amount of correction and processing time, it is crucial to reduce the carbon variation within the raw material. Prior art literature

[65535] Japanese Patent Publication No. 2003-147482 The problem to be solved

[0004] The present invention aims to solve such conventional problems by providing a non-heat-treated steel material for rack bars with excellent straightness and processability, and a method for manufacturing the same. However, this objective is exemplary and does not limit the scope of the present invention. means of solving the problem

[0005] According to one aspect of the present invention, a wire for a rack bar is provided.

[0006] The above-mentioned wire for a rack bar comprises, in weight%, C: 0.40~0.55%, Si: 0.10~0.40%, Mn: 1.00~1.50%, V: 0.01~0.20%, Cr: 0.05~0.30%, Ni: 0.05~0.30%, Al: 0.01~0.05%, S: 0.03~0.07%, Mo: 0.005~0.30%, and the remainder being Fe and unavoidable impurities, wherein the above-mentioned Cr and V satisfy the composition of the following formula (1), and in a cross-section perpendicular to the longitudinal direction of the wire, the diameter of the wire is D, and the carbon content at depths of 0.1D, 0.3D, and 0.5D from the surface of the wire toward the center is C, respectively. 0.1D , C 0.3D and C 0.5D When saying that, it may satisfy the following equations (2) and (3).

[0007] 0.10 ≤ [Cr]+[V] ≤ 0.50 … Equation (1)

[0008] 0.9 ≤ C 0.1D / C 0.3D ≤ 1.1 … Equation (2)

[0009] 0.9 ≤ C 0.3D / C 0.5D ≤ 1.1 … Equation (3)

[0010] The above [Cr] and [V] represent the content (weight%) of Cr and V, respectively.

[0011] According to one embodiment, the tensile strength of the wire is 750 MPa or higher, and the impact strength is 50 J / cm² 2 It can be characterized as being above.

[0012] According to one embodiment, the wire may further contain N:0.009~0.02%.

[0013] According to one embodiment, the wire may include at least one precipitate from the group consisting of VC, VN, AlN, and AlC on its surface.

[0014] According to one embodiment, the wire may include a ferrite and pearlite composite structure.

[0015] According to another aspect of the present invention, a method for manufacturing a wire for a rack bar is provided.

[0016] The method for manufacturing the above-mentioned wire rod for a rack bar comprises the step of manufacturing a steel billet by continuously casting a steel material containing, in weight percent, C: 0.40~0.55%, Si: 0.10~0.40%, Mn: 1.00~1.50%, V: 0.01~0.20%, Cr: 0.05~0.30%, Ni: 0.05~0.30%, Al: 0.01~0.05%, S: 0.03~0.07%, Mo: 0.005~0.30%, and the remainder being Fe and unavoidable impurities, using an electromagnetic stirring device (EMS) under conditions where the current value is 0~300A; and a step of manufacturing a wire rod by hot rolling and then coiling the steel billet; wherein Cr and V satisfy the composition of the following formula (1), and in a cross-section perpendicular to the longitudinal direction of the wire rod, the diameter of the wire rod is D, and the carbon content at depths of 0.1D, 0.3D, and 0.5D from the surface of the wire rod toward the center is C, respectively. 0.1D , C 0.3D and C 0.5D When saying that, the following equations (2) and (3) can be satisfied.

[0017] 0.10 ≤ [Cr]+[V] ≤ 0.50 … Equation (1)

[0018] 0.9 ≤ C 0.1D / C 0.3D ≤ 1.1 … Equation (2)

[0019] 0.9 ≤ C 0.3D / C 0.5D ≤ 1.1 … Equation (3)

[0020] The above [Cr] and [V] represent the content (weight%) of Cr and V, respectively.

[0021] According to one embodiment, the steel may further contain N:0.009~0.02%. Effects of the invention

[0022] According to an embodiment of the present invention as described above, a wire rod used in an automobile steering rack bar having excellent mechanical properties and impact toughness even without heat treatment, and a method for manufacturing the same can be provided.

[0023] Of course, the scope of the present invention is not limited by these effects. Brief explanation of the drawing

[0024] Figure 1 is the result of a carbon component deviation analysis according to one embodiment of the present invention. Figure 2 is a calibration evaluation result according to one embodiment of the present invention. Figure 3 is a processability evaluation result according to one embodiment of the present invention. Specific details for implementing the invention

[0025] Hereinafter, various embodiments of the present invention will be described in detail with reference to the attached drawings. The embodiments of the present invention are provided to more fully explain the present invention to those skilled in the art, and the following embodiments may be modified in various different forms, and the scope of the present invention is not limited to the following embodiments. Rather, these embodiments are provided to make the present disclosure more faithful and complete and to fully convey the spirit of the present invention to those skilled in the art. In addition, the thickness or size of each layer in the drawings is exaggerated for convenience and clarity of explanation.

[0026] According to one aspect of the present invention, a wire for a rack bar is provided.

[0027] The above-mentioned wire for rack bars comprises, in weight percent, C: 0.40~0.55%, Si: 0.10~0.40%, Mn: 1.00~1.50%, V: 0.01~0.20%, Cr: 0.05~0.30%, Ni: 0.05~0.30%, Al: 0.01~0.05%, S: 0.03~0.07%, Mo: 0.005~0.30%, and the remainder being Fe and unavoidable impurities.

[0028] The components added in the present invention will be described in detail below. Meanwhile, unless otherwise specified, "%" used herein means "weight%".

[0029] C : 0.40 ~ 0.55%

[0030] If the C content is 0.40% or less, the strength is insufficient, and if it is added in excess of 0.55%, toughness and ductility decrease due to the increase in strength. Therefore, the C content range is set to 0.40~0.55%.

[0031] Si : 0.10~0.40%

[0032] Si is an element that improves deformation resistance, but if added in an amount exceeding 0.40%, it significantly reduces drawability during cold drawing, and if added in an amount less than 0.10%, the effect of improving strength is low.

[0033] Mn : 1.00 ~ 1.50%

[0034] If the Mn content is less than 1.00%, the effect of securing strength is insufficient, and if it exceeds 1.50%, toughness may decrease due to the improvement in strength.

[0035] V : 0.01 ~ 0.20%

[0036] V is an element that reacts with C and N in steel to form V(C,N) complex precipitates. V-based precipitates with added V prevent precipitation strengthening and grain boundary coarsening, and act as ferrite nucleation sites during wire rod rolling to increase the ferrite fraction, thereby improving strength and toughness. When V is less than 0.01%, the precipitation strengthening effect is low, and when added in excess of 0.20%, the grain refinement effect is low and the increase in strength may reduce toughness.

[0037] Cr : 0.05 ~ 0.30%

[0038] If the Cr content is less than 0.05%, the effect of securing strength is low, and if more than 0.3% is added, it can significantly reduce drawability during cold drawing.

[0039] Ni : 0.05 ~ 0.30%

[0040] When the Ni content is less than 0.05%, the effect of improving impact toughness and fatigue properties is minimal. Meanwhile, since Ni is an expensive element, it is desirable to add it at 0.30% or less.

[0041] Al : 0.010 ~ 0.050%

[0042] Al cannot sufficiently form AlN at less than 0.010%, and mechanical properties may deteriorate when it exceeds 0.05%.

[0043] S : 0.03~0.07%

[0044] If S is added in an amount of less than 0.03%, sufficient improvement in processability cannot be expected, and if it is added in an amount of more than 0.07%, the toughness and fatigue properties of the material may be reduced due to a large amount of coarse MnS.

[0045] Mo : 0.005~0.30%

[0046] Mo forms various types of carbides with only a small amount of addition. However, Mo is an expensive element, and if added in excess of 0.30%, the cost increases, and the effect is not high relative to the amount added. Considering these characteristics, the range of Mo content is set to 0.005~0.30%.

[0047] N : 0.009~0.02%

[0048] N can be added as needed, and when added, it combines with aluminum (Al) and vanadium (V) at high temperatures to form Al and V composite nitrides, which lead to grain refinement and an increase in the ferrite fraction within the steel, thereby ultimately contributing to the improvement of the steel's impact toughness. If N is added in an amount exceeding 0.02%, it may form coarse precipitates depending on the Al content, which may actually lower the impact toughness.

[0049] The wire rod for a rack bar of one embodiment contains alloying elements satisfying the aforementioned alloy composition, and the remainder substantially comprises iron (Fe) and unavoidable elements. The unavoidable elements are elements contained depending on the conditions of raw materials, materials, manufacturing equipment, etc., and may be partially incorporated as impurities within a range that does not excessively impair the properties of the steel plate.

[0050] In the present invention, the tensile strength is 750 MPa or higher and the impact strength is 50 J / cm² 2 It provides an excellent non-heat-treated steel that simultaneously satisfies the above characteristics, specifically by securing strength through the addition of Cr and V, and securing impact toughness through the addition of Ni and Mo.

[0051] The above Cr and V satisfy the composition of the following formula (1).

[0052] 0.10 ≤ [Cr]+[V] ≤ 0.50 … Equation (1)

[0053] In Equation (1), [Cr] and [V] represent the content (weight%) of Cr and V, respectively.

[0054] If the sum of the Cr and V contents is less than 0.10%, the strength of the wire rod for the rack bar targeted in the present invention cannot be secured, and if it is greater than 0.50%, the impact toughness of the non-heat-treated steel may be reduced, so considering this, it is made to fall within the range of Equation (1).

[0055] The above steel has a ferrite and pearlite composite structure.

[0056] The steel for rack bars of the present invention described above can be manufactured as an example in the following manner.

[0057] Steel plate manufacturing stage

[0058] The steel billet manufacturing stage is a stage of continuously casting steel with, in weight percent, C: 0.40~0.55%, Si: 0.10~0.40%, Mn: 1.00~1.50%, V: 0.01~0.20%, Cr: 0.05~0.30%, Ni: 0.05~0.30%, Al: 0.01~0.05%, S: 0.03~0.07%, Mo: 0.005~0.30%, and the remainder being Fe and unavoidable impurities.

[0059] Blooms or billets in a semi-finished state can be obtained through the continuous casting process.

[0060] In the continuous casting process, an electromagnetic stirrer (EMS) is used to generate a magnetic field through an electric current to stir and mix the molten metal.

[0061] Specifically, an electromagnetic coil is placed along the path where the molten metal flows, and this coil is used to generate a magnetic field through an electric current. By supplying current to the coil, a magnetic field is formed around the coil by the current, and this magnetic field agitates and mixes the molten metal.

[0062] In an embodiment of the present invention, current is supplied to the coil under conditions where the current value is 0 to 300 A. The current value is a factor that significantly influences the reduction of carbon variation within the raw material, and this can affect straightness after high-frequency heat treatment.

[0063] In the case of the rack bar component according to the present invention, when high-frequency heat treatment is applied, the heat-affected zone (depth) on the tooth surface and the back surface differs due to the gear shape, and thermal deformation occurs as a result, requiring correction work. However, if there is a significant difference in the carbon content between the tooth surface and the back surface, which greatly influences the heat treatment characteristics, significant thermal deformation occurs, thereby increasing the amount of correction and working time. Therefore, it is important to reduce the carbon variation within the raw material.

[0064] Accordingly, in an embodiment of the present invention, the EMS current intensity was limited to 300A or less as a condition to reduce carbon variation within the raw material.

[0065] The resulting deviation in carbon composition is as follows.

[0066] As illustrated in FIG. 1(b), in a cross-section perpendicular to the longitudinal direction of the wire, the diameter of the wire is D, and the carbon content at depths of 0.1D, 0.3D, and 0.5D from the surface of the wire toward the center is C, respectively. 0.1D , C 0.3D and C 0.5D When saying that, it may satisfy the following equations (2) and (3).

[0067] 0.9 ≤ C 0.1D / C 0.3D ≤ 1.1 … Equation (2)

[0068] 0.9 ≤ C 0.3D / C 0.5D ≤ 1.1 … Equation (3)

[0069] In other words, the carbon content deviation ratio is within ±10%, allowing for a reduction in carbon variation within the raw material compared to conventional wire rods for rack bars.

[0070] Rolling and winding steps

[0071] Hot rolling is the step of manufacturing wire rod products by hot rolling a reheated steel billet.

[0072] During hot rolling, the finish rolling temperature may be in the A1 to A3 temperature range or between 700°C and 900°C. If the finish rolling temperature exceeds 900°C, decarburization may occur, or the formation of pearlite nucleation due to coarse grains may be delayed, and the deviation from the coiling temperature may increase, resulting in reduced temperature controllability. Conversely, if the finish temperature is too low, below 700°C, the rolling load becomes excessive.

[0073] When rolling as described above, at least one precipitate from the group consisting of VC, VN, AlN, and AlC is formed on the surface of the wire rod, and the ferrite fraction of the non-heat-treated steel can be increased during the rolling process. That is, V and Al(C,N) precipitates formed within the matrix of the base material effectively refine the grain size and act as ferrite nucleation sites during rolling, thereby maximizing the ferrite fraction within the matrix and ultimately increasing the impact toughness of the steering rack bar material.

[0074] In the coiling process, the steel billet is coiled by passing it through a laying head and kocks after hot rolling. Specifically, the temperature at which the billet is coiled by passing it through the laying head and kocks can be performed at 750°C to 830°C.

[0075] In the cooling process, the steel billet is cooled after coiling. Specifically, after coiling by passing it through a laying head and a coke, it is cooled while controlling the average cooling rate to 5℃ / s or less, for example, 0.3℃ / s to 5℃ / s. Through this, the grain size and microstructure fraction of the steel can be controlled.

[0076] The present invention will be explained in more detail below through examples.

[0077] The following examples are provided to sufficiently convey the concept of the present invention to those skilled in the art to which the present invention belongs, and the present invention is not limited to the examples presented herein and may be embodied in other forms.

[0078] Examples

[0079] 1. Experimental Example 1

[0080] A steel material having the composition system (unit: weight%) of Table 1 below was prepared, and for the steel material, the EMS current intensity was set to 300A or less, and reheating, rolling, and cooling were performed with a reheating temperature of 1100~1300℃, a final rolling temperature of A1~A3 temperature range, and a cooling rate of 1℃ / s or less to produce specimens of the comparative example and the example, respectively. Tensile strength and impact strength were measured for the specimens.

[0081] division C Si Mn S Ni Cr Mo V Al N(ppm) Cr+V Tensile strength (MPa) Impact strength (J / cm²) 2 ) Comparative Example 1 0.46 0.30 1.20 0.053 0.03 0.15 0.01 0.048 0.019 41 0.198 763 47 Comparative Example 2 0.45 0.25 1.22 0.053 0.03 0.15 0.01 0.001 0.019 82 0.151 748 45 Comparative Example 3 0.46 0.26 1.17 0.051 0.02 0.04 0.01 0.042 0.021 72 0.082 745 46 Example 1 0.46 0.30 1.20 0.055 0.06 0.14 0.01 0.049 0.020 91 0.189 785 53 Example 2 0.46 0.29 1.20 0.052 0.10 0.12 0.03 0.051 0.019 101 0.171 782 62 Example 3 0.45 0.29 1.18 0.048 0.12 0.15 0.04 0.048 0.014 105 0.198 791 71 Example 4 0.46 0.29 1.21 0.048 0.12 0.16 0.10 0.051 0.017 112 0.211 803 71

[0082] As can be seen from Table 1, in the case of Examples 1 to 4 satisfying the alloy composition proposed in the present invention, the tensile strength is 750 MPa and the impact strength is 50 J / cm² 2 It simultaneously satisfies the characteristics of the above. By adding Ni to medium carbon steel, low-temperature impact toughness and metal fatigue resistance are enhanced, and by efficiently adding the 'N' component, V, Al(C,N) precipitates are effectively formed. The V, Al(C,N) precipitates formed within the base material matrix effectively refine the grain size and act as ferrite nucleation sites during rolling, thereby maximizing the ferrite fraction within the matrix and ultimately increasing the impact toughness of the steering rack bar material.

[0083] On the other hand, in the case of Comparative Examples 1 to 3, the alloy composition proposed in the present invention was not satisfied, and it was found that the tensile strength and impact strength were inferior compared to the examples.

[0084] 2. Experimental Example 2

[0085] For the specimen of Example 1 above, the carbon component deviation and correctability were evaluated by changing the EMS conditions to 0~400A.

[0086] The results of the analysis of carbon component deviations are shown in Figure 1 and Table 2.

[0087] division EMS Conditions / (Carbon content wt.%) 0A 200A 300A 400A location 0.1D 0.452 0.446 0.436 0.402 0.2D 0.454 0.456 0.469 0.477 0.3D 0.451 0.458 0.459 0.455 0.4D 0.450 0.467 0.444 0.432 0.5D (CENTER) 0.455 0.443 0.42 0.412 0.6D 0.452 0.451 0.438 0.445 0.7D 0.461 0.457 0.452 0.462 0.8D 0.453 0.458 0.465 0.482 0.9D 0.450 0.447 0.435 0.421 Stone formation 0.1D / 0.3D 1.00 0.97 0.95 0.88 0.3D / 0.5D 0.99 1.03 1.09 1.10 0.7D / 0.5D 1.01 1.03 1.08 1.12 0.9D / 0.7D 0.98 0.98 0.96 0.91

[0088] It was confirmed that when the EMS condition is set to 0~300A, the following equations (2) and (3) are satisfied.

[0089] 0.9 ≤ C 0.1D / C 0.3D ≤ 1.1 … Equation (2)

[0090] 0.9 ≤ C 0.3D / C 0.5D ≤ 1.1 … Equation (3)

[0091] On the other hand, it was confirmed that in the case of the 400A condition, the above equations (2) and (3) are not satisfied. Here, C 0.1D ~ C 0.9D Since represents the distance from the surface of the wire to the center, C 0.1D / C 0.3D is C 0.9D / C 0.7D It can also be expressed as, and C 0.3D / C 0.5D is C 0.7D / C 0.5D It can also be expressed as.

[0092] In addition, the automotive steering parts (rack bars) produced by changing the above EMS conditions were subjected to high-frequency heat treatment and then straightened.

[0093] The calibration evaluation was performed by manufacturing and evaluating 200 parts.

[0094] The results of the calibration evaluation are shown in Fig. 2. In Fig. 2, (a) the TIR value is the value of 2,500 μm or more among 200 manufactured parts, and (b) the calibration count value is the value of 6 calibration counts among 200 parts.

[0095] As a result, as the EMS output decreased, the TIR (Total indicator reading) and the number of calibrations decreased. This can be explained by the effect of reducing thermal deformation due to the reduction of carbon deviation. It can be seen that when the EMS output exceeds 300A, productivity decreases as the number of final calibrations after heat treatment increases due to carbon deviation. Therefore, in the present invention, the EMS current intensity is limited to 300A or less.

[0096] 3. Experimental Example 3

[0097] To observe differences according to S content, the S content in the composition of Example 1 above was changed as shown in Table 3 below, and the machinability stress and fatigue characteristics were observed. The machinability test conditions were set to a cutting speed of 850 mm / s and a cutting depth of 0.13 mm for the MTS high-speed machining tester. The rotational bending fatigue evaluation is damage caused by fatigue stress resulting from repeated rotation or bending of the specimen, and the fatigue limit (stress up to 10 million rotations), which is the strength at which permanent fracture of the steel does not occur, was defined as the fatigue characteristic.

[0098] division C Si Mn S Ni Cr Mo V Al Processing stress (MJ / m 3 ) Fatigue characteristics (kgf / mm²) 2 ) Comparative Example 4 0.46 0.30 1.20 0.006 0.06 0.14 0.01 0.049 0.02 3213 38 Example 5 0.037 3073 36 Example 1 0.055 3015 36 Example 6 0.067 2979 35 Comparative Example 5 0.011 2732 32

[0099] Observing Table 3 and Figure 3, it was confirmed that Comparative Examples 4 and 5 had lower sulfur (S) content and therefore exhibited inferior processing stress and fatigue characteristics, respectively. Meanwhile, in the case of Examples 1, 5, and 6, the sulfur (S) content was within the compositional range of the present invention, which is 0.03 to 0.07 wt%, and it was confirmed that both processing stress and fatigue characteristics were excellent.

[0100] The present invention has been described with reference to the embodiments illustrated in the drawings, but this is merely illustrative, and those skilled in the art will understand that various modifications and equivalent alternative embodiments are possible therefrom. Accordingly, the true technical scope of protection of the present invention should be determined by the technical spirit of the appended claims.

Claims

Claim 1 In weight%, it comprises C:0.40~0.55%, Si:0.10~0.40%, Mn:1.00~1.50%, V:0.01~0.20%, Cr:0.05~0.30%, Ni:0.05~0.30%, Al:0.01~0.05%, S:0.03~0.07%, Mo:0.005~0.30%, N:0.009~0.02%, and the remainder being Fe and unavoidable impurities, and the wire rod comprises at least one precipitate selected from the group consisting of VC, VN, AlN, and AlC on its surface, and comprises a ferrite and pearlite composite structure, wherein the above Cr and V satisfy the composition of the following formula (1), and in a cross-section perpendicular to the longitudinal direction of the wire rod, the diameter of the wire rod is D, and a depth of 0.1D from the surface of the wire rod toward the center, The carbon content at the 0.3D and 0.5D positions is C, respectively 0.1D , C 0.3D and C 0.5D A wire for a rack bar satisfying the following equations (2) and (3). 0.10 ≤ [Cr]+[V] ≤ 0.50 … Equation (1) 0.9 ≤ C 0.1D / C 0.3D ≤ 1.1 … Equation (2) 0.9 ≤ C 0.3D / C 0.5D ≤ 1.1 … Equation (3) The above [Cr] and [V] represent the content (weight%) of Cr and V, respectively. Claim 2 In claim 1, the tensile strength of the wire is 750 MPa or higher, and the impact strength is 50 J / cm² 2 A wire for a rack bar characterized by the above. Claim 3 delete Claim 4 delete Claim 5 delete Claim 6 A step of manufacturing a steel billet by continuously casting a steel material containing, in weight percent, C: 0.40~0.55%, Si: 0.10~0.40%, Mn: 1.00~1.50%, V: 0.01~0.20%, Cr: 0.05~0.30%, Ni: 0.05~0.30%, Al: 0.01~0.05%, S: 0.03~0.07%, Mo: 0.005~0.30%, N: 0.009~0.02%, and the remainder being Fe and unavoidable impurities, using an electromagnetic stirring device (EMS) under conditions where the current value is 0~300A; a step of reheating the steel billet in the range of 1100~1300℃; The method comprises the step of manufacturing a wire rod by hot rolling the above-mentioned reheated steel billet at a finishing rolling temperature in the range of A1 to A3 or 700 to 900°C, and then coiling it at a temperature range of 750°C to 830°C; and the step of cooling the above-mentioned coiled wire rod at an average cooling rate of 0.3°C / s to 5°C / s; wherein the Cr and V satisfy the composition of the following formula (1), and in a cross-section perpendicular to the longitudinal direction of the above-mentioned wire rod, the diameter of the above-mentioned wire rod is D, and the carbon content at depths of 0.1D, 0.3D, and 0.5D from the surface of the above-mentioned wire rod toward the center is C, respectively. 0.1D , C 0.3D and C 0.5D A method for manufacturing a wire rod for a rack bar satisfying the following equations (2) and (3), wherein 0.10 ≤ [Cr]+[V] ≤ 0.50 … Equation (1) 0.9 ≤ C 0.1D / C 0.3D ≤ 1.1 … Equation (2) 0.9 ≤ C 0.3D / C 0.5D ≤ 1.1 … Equation (3) The above [Cr] and [V] represent the content (weight%) of Cr and V, respectively. Claim 7 delete

Citation Information

Patent Citations

  • Non-heatteated high strength and high toughness forging, and production method therefor

    JP2003147482A

  • Steel wire rod excellent in mechanical descalabilityand manufacturing method thereof

    KR1020030082997A

  • Method for manufacturing casting strip for wire cord with excellent surface quality

    KR1020100022287A